100 J-level pulse compression for peak power enhancement. (April 2017) - Mironov, S.Yu.; Wheeler, J.; Gonin, R.; Cojocaru, G.; Ungureanu, R.; Banici, R.; Serbanescu, M.; Dabu, R.; Mourou, G.; Khazanov, E.A.
Abstract: A possibility of using self-phase modulation and cascaded quadratic nonlinearity effects for the enhancement of the temporal intensity profile is analysed theoretically in application to petawatt pulses at a kJ energy level. Preliminary experiments at a petawatt CETAL laser facility demonstrate the reduction of a pulse duration from 46 fs down to 29 fs by using the self-phase modulation effect and consequent spectral phase correction. These efficient methods offer an opportunity to economically enhance existing laser facility intensities and offer a broader range of high-intensity physics to become more readily attainable.